2021
DOI: 10.7554/elife.63040
|View full text |Cite
|
Sign up to set email alerts
|

Brain endothelial cell TRPA1 channels initiate neurovascular coupling

Abstract: Cerebral blood flow is dynamically regulated by neurovascular coupling to meet the dynamic metabolic demands of the brain. We hypothesized that TRPA1 channels in capillary endothelial cells are stimulated by neuronal activity and instigate a propagating retrograde signal that dilates upstream parenchymal arterioles to initiate functional hyperemia. We find that activation of TRPA1 in capillary beds and post-arteriole transitional segments with mural cell coverage initiates retrograde signals that dilate upstre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 45 publications
2
78
0
Order By: Relevance
“…An analysis of the conduction kinetics of vasodilator signals revealed that the propagation velocity of vasodilatory signals was significantly slower following application of TRPA1 agonists onto capillaries compared with that following application of K + . A further comparison of different vascular segments confirmed these results, showing that signals initiated by TRPA1 channels propagate much more slowly through deeper regions of the capillary network than those initiated by K ir channel activation [ 110 ]. However, we also showed that, in the post-arteriole transitional segment—a mural cell-rich region that bridges deeper reaches of the capillary network with its feeding parenchymal arteriole [ 113 ]—signal propagation is rapid and comparable to that produced by activating K ir channels [ 108 , 110 ].…”
Section: Regulation Of Vascular Tone By Trpa1 Channelsmentioning
confidence: 73%
See 4 more Smart Citations
“…An analysis of the conduction kinetics of vasodilator signals revealed that the propagation velocity of vasodilatory signals was significantly slower following application of TRPA1 agonists onto capillaries compared with that following application of K + . A further comparison of different vascular segments confirmed these results, showing that signals initiated by TRPA1 channels propagate much more slowly through deeper regions of the capillary network than those initiated by K ir channel activation [ 110 ]. However, we also showed that, in the post-arteriole transitional segment—a mural cell-rich region that bridges deeper reaches of the capillary network with its feeding parenchymal arteriole [ 113 ]—signal propagation is rapid and comparable to that produced by activating K ir channels [ 108 , 110 ].…”
Section: Regulation Of Vascular Tone By Trpa1 Channelsmentioning
confidence: 73%
“…Using whole-cell patch-clamp electrophysiology, we determined that TRPA1 channels are present and functional on native brain capillary endothelial cells. In a series of ex vivo experiments utilizing a recently characterized isolated ex vivo microvascular preparation that allows for pressure myography studies of brain arteriole segments attached to their capillary branches [ 108 ], we found that direct application of the TRPA1 agonists AITC or 4-HNE onto distal capillary extremities elicited transient, reversible, and reproducible dilatation of the connected upstream parenchymal arteriole [ 110 ]. This response was diminished in preparations from Trpa1 -ecKO mice, or by superfusing the TRPA1 antagonist HC-030031 or severing the capillaries from their upstream arteriole in preparations from wild-type mice.…”
Section: Regulation Of Vascular Tone By Trpa1 Channelsmentioning
confidence: 99%
See 3 more Smart Citations